Revolutionizing cervical cancer diagnostics: A shift from traditional techniques to biosensors - Ubaid Mushtaq Naikoo; Roberto Pilloton; Humaira Farooqi; Jagriti Narang (Biosensors and Bioelectronics: X)
Cervical cancer is the most important contributor to ailment and death among females universally, highlighting the urgent need for effective diagnostic tools. Traditional diagnostic techniques, such as Pap smears and HPV testing, though effective, suffer from limitations including invasiveness, variable sensitivity, and dependence on clinical infrastructure. This review explores the transformative potential of biosensors as a non-invasive, cost-effective, and sensitive alternative for cervical cancer diagnostics. Comprehensive analysis of current biosensor technologies, emphasizing their mechanisms, advantages, and potential to overcome the drawbacks of conventional methods. Furthermore, the review discusses recent advancements in biosensor design, including integrating nanomaterials and point-of-care systems, which enhance their diagnostic accuracy and accessibility. Key challenges in the clinical translation of biosensors are also addressed, along with potential solutions and future research directions. By highlighting the shift from traditional techniques to biosensors, this review underscores the promise of these innovative tools in improving early detection and patient outcomes in cervical cancer care.